1993
DOI: 10.1002/jez.1402660305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an antiandrogen treatment on the antler cycle of male fallow deer (Dama dama L.)

Abstract: Weekly application of the antiandrogen cyproteron acetate (CA) to 3 adult (group 1, treatment starting 3 weeks prior to the rut) and 4 subadult (group 2, treatment starting after the rut) fallow bucks led to premature antler casting after about 9 weeks (group 1) or 16 to 17 days (group 2). Variation in time span between onset of CA administration and induced casting (in late November/early December) is attributed to age- and season-dependent differences in androgen levels before and during the treatment period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…; Lincoln, ; Kierdorf et al. , ). This suggests that higher androgen levels inhibit osteoclast formation in the pedicle, which would otherwise occur as a consequence of the death of the antlers due to insufficient blood supply and the attempt of the organism to sequester the dead bone (Goss, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lincoln, ; Kierdorf et al. , ). This suggests that higher androgen levels inhibit osteoclast formation in the pedicle, which would otherwise occur as a consequence of the death of the antlers due to insufficient blood supply and the attempt of the organism to sequester the dead bone (Goss, ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies on the bone architecture of hard antlers were predominantly conducted in larger species, especially red deer and fallow deer ( Dama dama ; Kierdorf et al. , , ; Rolf & Enderle, ; Chen et al. ; Launey et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously suggested that both osteoclastic activity in the distal pedicle and the onset of antler regeneration are repressed for some months following velvet shedding from the antlers, with high levels of circulating androgens playing a major role in this process (Bubenik, 1983;Kierdorf and Kierdorf, 1992a,b;Kierdorf et al, 1993). Thus, in contrast to limb regeneration in urodeles, which starts immediately after the loss of a limb or limb portion, there is a considerable lag-time between velvet shedding from, and death of, the bony antler and the onset of the regenerative process.…”
Section: Basic Aspects Of Antler Regeneration and Comparison With Limmentioning
confidence: 99%
“…Castration of male deer carrying hard antlers as well as the administration of substances interfering with testosterone production or inhibiting both testosterone production and its action at the receptor level causes premature antler casting (Wislocki et al, 1947;Lincoln, 1971;Muir et al, 1982;Jaczewski, 1985;Bubenik GA et al, 1987, 2002Goss et al, 1992;Schams et al, 1992;Kierdorf U et al, 1993Suttie et al, 1995). Administration of testosterone or estradiol to males in hard antler postpones antler casting beyond the normal date (Goss, 1968).…”
mentioning
confidence: 99%